Long-term effect of whole body vibration training on jump height: meta-analysis - Manimmanakorn, N.; Hamlin, M. J.; Ross, J. J.; Manimmanakorn, A. (The Journal of Strength and Conditioning Research, 2014)
Whole body vibration (WBV) is widely promoted as a means of improving muscle strength, but the evidence of a performance benefit is unclear with some reporting improvements and others finding none. The objective of this study was to analyze the current evidence for the effectiveness of WBV on jump height. We included randomized controlled trials or matched design studies comparing the effect of WBV training on countermovement and squat jump (SJ) height, which were gathered from MEDLINE, Web of Knowledge, Sciencedirect, Proquest, Scopus, Google Scholar, and SPORTDiscus databases. The overall effect of WBV training (from the 15 studies included) compared with having no additional exercise on countermovement jump height yielded a positive standardized mean difference of 0.77 (95% confidence interval, 0.55-0.99). The effect of WBV training on SJ height was 0.68 (0.08-1.11). Vibration exercise consisting of a higher frequency (>30 Hz, 0.86, 0.62-1.10), higher amplitude (>3 mm, 0.84, 0.52-1.17), longer exposure duration (>10 minutes per session, 0.92, 0.48-1.36), longer training period (>12 weeks, 0.87, 0.56-1.19) and among nonathletes (0.96, 0.63-1.30) had greater benefit for jump height improvement than a lower frequency (?30 Hz, 0.56, 0.13-0.99), lower amplitude (?3 mm, 0.66, 0.35-0.98), shorter exposure duration (?10 minutes per session, 0.68, 0.45-0.92), intermediate training period (4-12 weeks, 0.72, 0.35-1.09), shorter training period (<4 weeks, 0.58, -0.08 to -1.23) and in athletes (0.59, 0.31-0.88). The effect of WBV training compared with a standard cardiovascular-type exercise group from 4 studies was 0.63 (0.10-1.15). In conclusion, WBV training produces a moderate-to-large effect on jump height. Vibration training protocols with higher frequencies, higher amplitudes, longer exposures per session, and longer training periods are more likely to enhance muscle power.